Crescimento e nutrição de plantas de leucena (Leucaena leucocephala (Lam.) R. de Vit) sob salinidade - Freire, Antonio Lucineudo de Oliveira; Rodrigues, Teresinha de Jesus Deléo [UNESP]; de Miranda, José Romilson Paes (My University, 2010)
Excessive salt can to promote water soil retention, reducing your availability to plants. Besides, they can interfere in protoplasm metabolism. The plants ability to survive in salinity conditions is an important factor to geographic distribution and agriculture in salinized regions. The objective of this work was to verify the effects of the NaCl in the growth, dry matter distribution and N, K, Ca, Mg, Na, and Cl content in young plants. The experiment was conducted in 'Leonard' pots, with nutrient solutions, with NaCl (0, 25, 50 and 100 mmol L-1). Increasing of NaCl concentration reduces growth and total dry matter. There was an increase of N and K content, in shoots, and N and Mg content in roots. There was an reduction in Mg content in shoots, and reduction of Ca content in roots with increasing of NaCl. Leucaena plants were inefficient to exclude Na and Cl, in shoots principally.
Growth and mineral nutrition of Leucaena leucocephala (Lam.) R. de Vit) in relation to salinity
Keywords: NaCl; Nutrients accumulation; Salinity